Comparative Efficacy of Prolactin inhibitors and PGF2α analogue in Bitches Affected with Cystic Endometrial Hyperplasia-Pyometra Complex - Madhwwani, R; Bhardwaj, A; Aich, R; Shivhare, M; Shivkumar, S; Mangrole, V (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was carried out at the Veterinary Clinical Complex, College of Veterinary Science and Animal Husbandry, Mhow and in private clinics across Indore on 30 bitches suffering from Cystic Endometrial Hyperplasia-Pyometra Complex (CEH-PC). The animals were randomly subdivided into five groups each of six bitches and treated with bromocriptine (1 μg/kg POx5 days) and cabergoline (5 μg/kg POx5 days) alone and in combination with cloprostenol (5 μg/kg s/c on day 0, 2 and 6) (Gr II to V) together with enrofloxacin (10-20 mg/kg PO, SID×5 days) + combination of metronidazole and povidone-iodine IU (5-10 ml×3 days), the later served as routine control Gr I.The treatment response of animals was evaluated through clinical, ultrasonographical, haematological and biochemical parameters. Blood samples were collected from cephalic or saphenous vein just before treatment (day 0) and after treatment on day 6 and day 14. Treatment approach -III (cabergoline 5 μg/kg POx5 days) was found to be the most effective without side effects with significant decrease in uterine luminal diameter after treatment. The results showed significant improvement in haemato-biochemical attributes in dogs affected with CEH-P complex following treatment IV and V, i.e. with use of bromocriptine and cabergoline in combination with cloprostenol as compared to other groups. Altered haematology and elevated serum The Cystic Endometrial Hyperplasia-Pyometra Complex (CEH-PC) is one of the most serious and common uterine diseases in bitches; defined as acute or chronic, polysystemic, diestrual disorder characterized by hyperplasia of the endometrium and infiltration of inflammatory cells that may involve all layers of the uterus (Zdunczyk et al., 2006). Clinical signs that can be observed in bitches with pyometra are anorexia, lethargy, abdominal distension, listlessness, polydypsia, polyuria, vomiting and fever (Bondade, 2006). creatinine, urea and other metabolites have been documented due to endotoxin induced damage to the vital organs (Dabhi and Dhami, 2006; Shah et al., 2017 and Alok Kumar and Atul Saxena, 2018).